The behaviour of liquid consonants in the Tambirat Malay dialect: An optimality-theoretic account - Mohd Zulkanien Sarbini, (Journal of Modern Languages, 2025)
Given its diverse population, Sarawak exhibits a remarkable degree of linguistic variation. Among its varieties is the Tambirat Malay dialect, a unique and understudied subdialect spoken in Kampung Tambirat, Samarahan. This study is an attempt to model the phonological behaviour of liquid consonants in this dialect, an aspect that has been overlooked by prior research. This study uses primary data collected from native speakers through interviews and the citation method with the Swadesh 200-word list as the primary instrument. Offering insights from the constraint-based approach, this study reveals that the rhotic [ɣ] is completely excluded in syllable codas, and to avoid this, deletion is employed as a repair strategy. The lateral [l], on the other hand, is allowed in a coda only when the preceding vowel is [e]. This restriction arises from the dialect’s general avoidance of coda [l], and as a resolution, it is typically substituted by the high vowel [j]; however, since this substitution will yield the diphthong [ej], which is marked and ill-formed, this process is blocked by the constraint NO-[ej]. The analysis shows that ALIGN-RHOTIC must be highly ranked, but NO-[ej] must dominate ALIGN‑LATERAL to eliminate candidates with the diphthong [ej]. IDENT‑IO[+lateral] and MAX-IO[+rhotic], on the other hand, must be ranked low to ensure that the candidates with ɣ-deletion and l-substitution emerge as the optimal outputs. Ultimately, the following partial constraint ranking is developed: ALIGN-RHOTIC, DEP-IO, MAX-IO[–rhotic], IDENT‑IO[–lateral], NO-[ej] >> ALIGN‑LATERAL >> MAX-IO[+rhotic], IDENT‑IO[+lateral]. Beyond its theoretical significance, this study is crucial for the documentation of Sarawak’s subdialects, many of which are gradually undergoing extinction due to language shift and urbanization.